Education and bilingualism - Cuculiza, María Nelly (1987)
Siguán and Mackey, classics of the literature on bilingualism, have just published this useful overview of studies on education and bilingualism, one of the few global views on the subject. The book is published with the support of the International Office of Education in Geneva and is of considerable value insofar as accounting for a bibliography as extensive as that of bilingualism is already a feat in itself. Another problem in undertaking such a task is the little agreement that exists among specialists due to the ambiguity and variable extension of the term bilingualism. Finally, we must not forget that the contact of languages ​​and cultures poses many problems of various types and magnitudes with the consequence of the multiplication of educational approaches and policies.